Estimation of sea level height variability in Cyprus using Sentinel-3 satellite altimetry data - Pekri, Marina; Danezis, Chris (My University, 2020)
The advent of satellite altimetry brought a revolution in monitoring sea level height in ocean and offshore areas. Satellite altimetry missions are constantly evolving over time and provide valuable products that assist, among others, in the precise estimation of Mean Sea Level (MSL) and its periodic update. Over the recent years, MSL has seen a rapid rise, mainly due to climate change and the increase of global temperature, which accelerates the melting of onshore snow and ice reserves, along with the thermal expansion of the oceans. Concordantly, several islands and coastal regions face the danger of 'drowning' or flooding. Therefore, Cyprus, being an island in the Southeastern region of the Mediterranean Sea mandates the continuous monitoring of sea level to determine the risk of flooding, especially in coastal zones. This paper presents a first endeavor to estimate MSL in Cyprus using Copernicus Sentinel-3 altimetric data from 2016 to date. The results were validated against MSL observations from the Cyprus national tide gauge network and a discussion on the use of Sentinel-3 data as an indispensable monitoring tool is carried out.
Keywords: Cyprus; Mean Sea Level; Satellite Altimetry; Sentinel-3; Tide Gauge